PENGARUH DIRECT MARKETING TERHADAP KEPUTUSAN PEMBELIAN DALAM MENGGUNAKAN SOCIAL EVENT PACKAGE DI ART DECO LUXURY HOTEL & R.docx - Savira Maulana; Nungky Puspita; Yosi Erfinda (Fakultas Pariwisata Universitas Pancasila, 2022)
The problem studied in this study is the decrease in the number of guests who use the social event package at Art Deco Luxury Hotel & Residence Bandung, this problem must be addressed immediately so that it does not become an obstacle for the hotel. This study aims to find out an overview of the implementation of direct marketing, an overview of purchasing decisions in using the social event package at Art Deco Luxury Hotel & Residence Bandung, and how direct marketing influences in an effort to improve purchasing decisions in using the social event package at Art Deco Luxury Hotel & Residences. Residence Bandung. This research uses descriptive quantitative method. The number of samples in this study were 83 respondents who had used the social event package at Art Deco Luxury Hotel & Residence Bandung. The sampling technique used is purposive sampling. The analysis technique used is multiple linear regression. Hypothesis testing in this study uses the coefficient of determination test, f test and t test. The results of this study indicate the implementation of direct marketing, purchasing decisions in using the social event package, and the influence of direct marketing on purchasing decisions in using the social event package at Art Deco Luxury Hotel & Residence Bandung. The results show that part of direct marketing and the decision to use the social event package is in the high category, and gets the best response, namely telemarketing and online channels. Direct marketing has an effect on purchasing decisions in using the social event package at Art Deco Luxury Hotel & Residence Bandung.